Integrated Science Learning Design Based on Local Wisdom of Wetlands to Improve High-Order Thinking Skills (HOTS) of Junior High School Students - Yudha Irhasyuarna; Fahmi (Postgraduate, University of Mataram, 2026)
This study aims to develop and evaluate an integrated science learning design based on wetland local wisdom to enhance junior high school students’ Higher Order Thinking Skills (HOTS). The study addresses the limited integration of local environmental contexts in science instruction, which often leads to low student engagement and suboptimal development of higher-order cognitive skills. A Research and Development (R&D) approach was employed using the 4D model (Define, Design, Develop, Disseminate). The developed products included lesson plans, integrated teaching materials, student worksheets, and HOTS-based assessment instruments designed to facilitate contextual and meaningful learning experiences. The validity of the developed learning design was assessed by experts, resulting in a high average validation score of 0.92, indicating strong content, construct, and language appropriateness. Practicality was evaluated through classroom implementation and student responses, showing a high implementation rate (94%) and positive student responses (88.5%), both categorized as very practical. The effectiveness of the learning design was measured using N-gain analysis, which yielded a score of 0.72, indicating a high level of improvement in students’ HOTS. Statistical analysis further confirmed significant improvements (p < 0.05), particularly in analytical (C4) and evaluation (C5) skills. In conclusion, the developed learning design is empirically proven to be valid, practical, and effective in improving students’ HOTS. It also provides a robust and innovative framework for contextual science learning through the integration of wetland local wisdom, contributing to the advancement of science education in environmentally relevant contexts